THE INFLUENCE OF MICRO, SMALL AND MEDIUM ENTERPRISES ON INTERPERSONAL COMMUNICATION BEHAVIOR FOR COMMUNITIES IN MEDAN CITY - Saefullah Saefullah; Muhammad Alfikri (KABILAH : Journal of Social Community, 2022)
Abstract: Small and Medium Enterprises (MSMEs) activities are one of the business fields that can develop and be consistent in the national economy. Micro, small and medium enterprises (MSMEs) are a good starting point for the formation or creation of jobs that are planned either by individuals, the private sector or even individuals. The purpose of this study was to determine the effect of interpersonal communication on interpersonal communication behavior for people in the city of Medan. The method used is descriptive qualitative descriptive narrative. Data collection techniques using observation, interviews, and documentation. The results of the study show that interpersonal communication behavior influences the development of micro, small and medium enterprises (MSMEs) in Medan City supported by four factors, namely audience, media, messages and communicators. The community's interpersonal communication behavior in determining the audience by collecting data on micro, small and medium entrepreneurs (MSMEs) is then selected according to the criteria included in fostering development programs. The media used are group media, print media, and online media to communicate information and knowledge to business owners. Then the influence in determining the communicators are people who have knowledge about MSMEsand are selected according to their experience and expertise. Keywords: Communication, Interpersonal Communication, MSMEs